Experimental investigation of the thermal runaway and fire characteristics of overcapacity lithium-ion batteries for electric bicycles in charging cabinets - Liu, Jie; Wang, Wei; Wang, Zhengyang; Wang, Hao; Kang, Yutao; Yang, Juntao (Frontiers in Energy Research, 2025)
Lithium-ion batteries (LIBs) are extensively used worldwide in the field of electric bicycles. However, the integration of LIBs that exceed the standards in certain electric bicycles has been associated with a significant increase in the propensity for fire-related hazards. In this study, the combustion behavior of electric bicycle ternary LIBs that exceed the standards was investigated through full-scale fire tests conducted in cabinet environments. LIB packs at two states of charge (SOC), 80% and 60%, were systematically exposed to controlled thermal abuse. This enabled comprehensive characterization of their combustion behavior and thermal propagation dynamics following ignition. The experimental results demonstrated that thermal runaway (TR) was initiated at 300 °C and progressed through four distinct phases: stable temperature rise (15 °C–20 °C/s), smoke-emitting TR, jet flame overflow, and stable combustion. The smoke emission duration was extended to 480 s under the 60% SOC condition, representing a 35% increase compared with 80% SOC, while the jet flame overflow duration was reduced by 200 s. The total smoke production at 60% SOC was eight times greater than that at 80% SOC, corresponding to a 57% increase in the peak heat release rate (107 kW vs. 68 kW). The vertical flame spread intensity under closed cabinet conditions exhibited a 3.3:1 predominance over horizontal propagation, with the maximum ceiling temperature reaching 495 °C (80% SOC), compared with <150 °C in the lateral compartments. These findings establish critical benchmarks for fire suppression system design in LIBs storage applications.